2021
DOI: 10.1186/s40900-021-00263-4
|View full text |Cite
|
Sign up to set email alerts
|

The attitudes of healthy children and researchers towards the challenges of involving children in research: an exploratory study

Abstract: Background A growing trend in research is to involve co-researchers. It is referred to as Patient and Public Involvement (PPI) and comprises three groups: the patients, the public, and the researchers. Like in adult public involvement, healthy children can also be considered as ‘the public’. Paediatric patients and researchers experienced in conducting child-inclusive research are often asked about their attitudes towards the challenges they encounter. This is not the case for healthy children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…is one way to keep children and families motivated, especially for long-term projects/activities such as YPAG membership. However, similar to other published research findings [ 18 , 23 , 24 ] we found in some of the case studies that this level of training was viewed as unnecessary when children and families preferred informal conversational approaches to help them understand their roles. Thus, adopting a more flexible, informal induction into the activity with clear terms of reference, consent documentation and support from the PPI facilitator was felt to be sufficient.…”
Section: Discussionsupporting
confidence: 90%
“…is one way to keep children and families motivated, especially for long-term projects/activities such as YPAG membership. However, similar to other published research findings [ 18 , 23 , 24 ] we found in some of the case studies that this level of training was viewed as unnecessary when children and families preferred informal conversational approaches to help them understand their roles. Thus, adopting a more flexible, informal induction into the activity with clear terms of reference, consent documentation and support from the PPI facilitator was felt to be sufficient.…”
Section: Discussionsupporting
confidence: 90%
“…These findings will inform the development of guidelines on involving adolescents in health research. The need for a comprehensive set of guidelines and resources on involving adolescents in health research has been highlighted by youth researchers81 and studies 83 106–109. These guidelines will facilitate researchers to collaborate with adolescents more effectively, leading to more meaningful involvement of adolescents in research.…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of being part of a YPAG for children, researchers, and research itself are well-recognised [4,6,9]. The establishment of the ROLO YPAG is a stepforward in enabling the ROLO children and their siblings voices and thoughts to be translated into research questions of importance.…”
Section: Discussionmentioning
confidence: 99%
“…Collaboration with Young Person's Advisory Groups (YPAGs) is one model that empowers children by involving them in decision making and action planning, while increasing confidence and research skills [3,4,6]. This can improve recruitment and retention rates, guide the acceptability and feasibility of studies, and increase research relevance [3,4,9].…”
Section: Introductionmentioning
confidence: 99%